Comparative study of arthroscopic treatment of osteochondral lesions of the talus - de Oliveira Felix Guerra, Isadora; Miranda Ramos Borges, Rodrigo; Moraes Gomes Damasceno Amorim, Miguel; Guimarães Huyer, Rodrigo; Douglas Bertelli, Hallan; Pedrão da Silva, Leonardo; Cillo, Mario Sergio Paulillo de (Journal of the Foot & Ankle, 2024)
Objectives: Evaluate and compare, through the American Orthopedic Foot and Ankle Society (AOFAS) score, the clinical and functional results of arthroscopy treatment of osteochondral lesions of the talus with bone marrow stimulation with or without association with the autologous matrix-induced chondrogenesis. Methods: A retrospective comparative clinical study with 56 patients diagnosed with osteochondral lesions of the talus, eight of whom did not agree to participate in the study, 35 were submitted to surgical treatment with subchondral bone microperforation, and 13 to microperforation associated with collagen matrix membrane. The Mann-Whitney test was applied to compare continuous measurements between the two groups. The significance level adopted for the statistical tests was 5%. Results: After intragroup analysis, the microperforation treatment group associated with collagen matrix membrane, all patients improved the AOFAS score (55.0 to 90.0). In the treatment with bone marrow stimulation, patients increased the AOFAS from 57.0 to 90.0. In the treatment with collagen matrix membrane, patients increased the AOFAS score from 51.0 to 90.0. There was no significant difference between the groups studied. Conclusion: Both treatments, through ankle arthroscopy, can be great treatment options for osteochondral lesions of the talus, according to their specific indications, with significant functional and clinical improvement, identified by the increase in the AOFAS score. Level of Evidence III; Retrospectivef comparative study; Therapeutic studies - investigating the results of treatment.